WITHDRAWN: Microfabrication of dissolvable, swellable, and biodegradable polymeric microneedle arrays - (:unkn) unknown (My University, 2012)
This article has been withdrawn at the request of the authors. The Publisher apologizes for any inconvenience this may cause. The full Elsevier Policy on Article Withdrawal can be found at http://www.elsevier.com/locate/withdrawalpolicy.